IDENTIFICATION FUNGI OF COMET FISH (Carrasius auratus) BY CONVENTIONAL AND PCR (Polymerase Chain Reaction) METHOD - Christin Natalia; Henni Syawal; Morina Riauwaty Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Fungal are a group of microbes that often cause disease in comet fish. Diseases caused by fungi are secondary infections, and can cause more than 50% death. The objective of the study was to find out the species of pathogenic fungi in comet fish and what is the prevalence of fungi that infect comet fish. The method used was survey at the location of the Ornamental Fish Shelter, Jalan Bukit Barisan, Tangkerang Timur Village, Tenayan Raya District, Pekanbaru City. The fish used were 6 - 8 cm as many as 15 tails . Conventional identification includes macroscopic inspect of fungi colonies and microscopic of fungi hyphae. Molecular identification was carried out by PCR (Polymerase Chain Reaction) technique and analyzed with Bioedit, BLASTn and MEGA applications to find out the phylogenetic tree. Research parameters include hyphae size and fungi prevalence. The results of conventional identification techniques found the 4 species of fungi, includes Aspergillus niger, Penicillium sp., Curvularia sp., Fusarium sp.. The result of molecular identification techniques found the species of fungi, includes Curvularia pseudorobusta with homolog value 93%, Trametes corrugate with homolog value 99%.,The conclusion from the identification results found two types of fungi that are pathogenic in comet fish, includes Fusarium sp. and Curvularia sp.. Fungal prevalence from 15 samples was 73,3%. Wide hyphae of fusarium sp. is 1,09 µm, and Curvularia sp. is 1,52 µm. Keywords: Fusarium sp., Curvularia sp., Carassius auratus.